Forebrain projection neurons target functionally diverse respiratory control areas in the midbrain, pons, and medulla oblongata. Issue 9 (5th January 2021) - Trevizan‐Baú, Pedro; Dhingra, Rishi R.; Furuya, Werner I.; Stanić, Davor; Mazzone, Stuart B.; Dutschmann, Mathias
Abstract: Eupnea is generated by neural circuits located in the ponto‐medullary brainstem, but can be modulated by higher brain inputs which contribute to volitional control of breathing and the expression of orofacial behaviors, such as vocalization, sniffing, coughing, and swallowing. Surprisingly, the anatomical organization of descending inputs that connect the forebrain with the brainstem respiratory network remains poorly defined. We hypothesized that descending forebrain projections target multiple distributed respiratory control nuclei across the neuroaxis. To test our hypothesis, we made discrete unilateral microinjections of the retrograde tracer cholera toxin subunit B in the midbrain periaqueductal gray (PAG), the pontine Kölliker‐Fuse nucleus (KFn), the medullary Bötzinger complex (BötC), pre‐BötC, or caudal midline raphé nuclei. We quantified the regional distribution of retrogradely labeled neurons in the forebrain 12–14 days postinjection. Overall, our data reveal that descending inputs from cortical areas predominantly target the PAG and KFn. Differential forebrain regions innervating the PAG (prefrontal, cingulate cortices, and lateral septum) and KFn (rhinal, piriform, and somatosensory cortices) imply that volitional motor commands for vocalization are specifically relayed via the PAG, while the KFn may receive commands to coordinate breathing with other orofacial behaviors (e.g., sniffing, swallowing). Additionally, we observed that the limbic or autonomic (interoceptive) systems are connected to broadly distributed downstream bulbar respiratory networks. Collectively, these data provide a neural substrate to explain how volitional, state‐dependent, and emotional modulation of breathing is regulated by the forebrain. Abstract : Respiratory motor activity can be modulated by higher brain inputs. We hypothesized that forebrain regions send descending inputs to the respiratory control areas in the midbrain, pons, and medulla. Our data imply that (a) volitional motor commands for vocalization are specifically relayed via the midbrain periaqueductal gray; (b) commands to coordinate breathing with other orofacial behaviors (e.g., sniffing, whisking, swallowing) target the pontine Kölliker‐Fuse nucleus, predominantly; and (c) limbic or autonomic (interoceptive) systems are connected to broadly distributed downstream brainstem respiratory networks, including the medullary Bötzinger complex (BötC), pre‐BötC, and caudal raphé nuclei. We provide a neural substrate to explain how volitional, state‐dependent, and emotional modulation of breathing is regulated by the forebrain.